Susceptibility of Male who Have Sex with Male to High-Risk Type Human Papillomavirus (HPV) 16 and 18 with Condyloma Acuminata - Prasetyadi Mawardi; Danu Yuliarto (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Condyloma acuminatum (CA) or genital warts are sexually transmitted infections caused by human papillomavirus (HPV). It is estimated that CA occurs in >80% of reproductive age in many countries, with the most common subtypes being 6 and 11. Purpose: The aim of the study to reveal the high risk (HR)-HPV in various condyloma acuminata in Dr. Moewardi Hospital. Methods: This study was a cross-sectional analytical observational study that assessed data collection concurrently over time. Specimens were patients diagnosed with condyloma acuminatum, biopsies were performed, and immunohistochemical staining was also performed. The sampling technique used sequential sampling, and the inclusion criteria included patients who came to our hospital for treatment. Results: The majority of the male sample was MSM. According to HIV status, 6 (30%) male patients were found to be positive. Immunohistochemistry showed that 15% of the samples were HR-HPV. Statistical test results for HR-HPV and low-risk (LR) HPV were significant, p-value = 0.038. Conclusion: Condyloma acuminatum is a sexually transmitted infection that usually occurs at the same time as HIV infection. In our study all patients with HR-HPV were MSM.